Coupling Hierarchical Ultrathin Co Nanosheets With N-Doped Carbon Plate as High-Efficiency Oxygen Evolution Electrocatalysts - Wang, Yue; Li, Meng; Zhou, Qixing; Wang, Qin; Zhang, Xingyuan; Sun, Dongmei; Tang, Yawen (Frontiers in Nanotechnology, 2021)
The rational design of cost-effective and highly efficient catalysts for the oxygen evolution reaction (OER) is vastly desirable for advanced renewable energy conversion and storage systems. Tailoring the composition and architecture of electrocatalysts is a reliable approach for improving their catalytic performance. Herein, we developed hierarchical ultra-thin Co nanosheets coupled with N-doped carbon plate (Co-NS@NCP) as an efficient OER catalyst through a feasible and easily scalable NaCl template method. The rapid dissolution-recrystallization-carbonization synthesis process allows Co nanosheets to self-assemble into plenty of secondary building units and to distribute uniformly on N-doped carbon plate. Benefitting from the vertically aligned Co nanosheet arrays and hierarchical architecture, the obtained Co-NS@NCP possess an extremely high specific surface area up to 446.49 m2 g−1, which provides sufficient exposed active sites, excellent structure stability, and multidimensional mass transfer channels. Thus, the Co-NS@NCP affords remarkable electrocatalytic performance for OER in an alkaline medium with a low overpotential of only 278 mV at 10 mA cm−2, a small Tafel slope, as well as robust electrocatalytic stability for long-term electrolysis operation. The present findings here emphasize a rational and promising perspective for designing high-efficiency non-precious electrocatalysts for the OER process and sustainable energy storage and conversion system.